Designing an Information System “Online Cashier (OK)” - Nadiza Lediwara; Sembada Denrineksa Bimorogo; Aulia Khamas Heikmakhtiar; Alvin Reychan Perdana Putra; Dicky Daniel Simarmata; Muhamad Alroy Rizky Pasha Ponto; Alfian Habib Ahmed; Regifia Ningrum Nur Aulia (Journal of Defense Technology and Engineering, 2025)
Micro, Small, and Medium Enterprises (MSME) play a crucial role in Indonesia’s economy, yet many still face obstacles in adopting digital technology, particularly in financial transaction recording, which often leads to inefficiency and errors. This study aims to design and develop an “Online Cashier (OK)” system as a solution for Warung Makan Soto Lamongan Cak Munif, which still relies on conventional transaction methods. The system was developed using the Agile method, emphasizing iterative and adaptive development tailored to user needs. The design process applied system modeling tools, including Use Case, Activity, and Class Diagrams, while system performance was evaluated through Black Box Testing. The results showed that the Online Cashier system achieved an overall design success rate of 98.75% and testing effectiveness of 94%, with features such as transaction recording, inventory management, user access control, and report generation functioning properly. The system significantly improves transaction accuracy, reduces operational inefficiency, enhances financial data transparency, and strengthens business management control. Furthermore, the Online Cashier (OK) system provides an opportunity for MSME owners to become more familiar with digital business management, supporting the broader agenda of digital transformation in Indonesia. This study implies that the implementation of web-based cashier systems can enhance MSME competitiveness by enabling structured, efficient, and data-driven decision-making.